Knowledge levels of fetal rights in Turkish pediatric nurses - Selen OZAKAR AKCA; Ahu Pınar TURAN; Dilek KALKAN YALCIN (Universa Medicina, 2022)
BACKGROUNDFetal rights are violated due to acts such as negligence, ignorance, false beliefs and substance addiction. Pediatric nurses, as defenders of the fetus, should inform pregnant women and the family about the rights of the fetus and assist the family in the decision-making process. This study aims to determine the knowledge levels of pediatric nurses on fetal rights. METHODSThis cross-sectional study involved 121 nurses working in the pediatric clinic of a training and research hospital. Data about characteristics of pediatric nurses and knowledge levels about fetal rights were collected. Statistical analyses were made with SPSS package program. Mann Whitney U test and Kruskal Wallis test was used to analyse the data. RESULTSIn this study, it was found that 76.9% of the pediatric nurses participating in the study did not have prior knowledge about fetal rights. There was a statistically significant difference between the participants’ mean scores of knowledge levels about fetal rights and their age, educational status, status of prior knowledge about fetal rights and where this knowledge was gained (p<0.05). CONCLUSIONAs a result, it was found that most of the pediatric nurses did not have prior knowledge about fetal rights, and that their knowledge about fetal rights was lacking. Considering that pediatric nurses, as the defenders of the fetus, have a duty to inform the family about fetal rights, it is recommended to plan trainings on fetal rights for pediatric nurses.